PTSD prevalence and associated risk factors after a fire disaster that broke out in a paediatric hospital: a cross-sectional study - Zaffina, Salvatore; Camisa, Vincenzo; Monducci, Elena; Vinci, Maria Rosaria; Vicari, Stefano; Bergamaschi, Antonio (La Medicina del Lavoro, 2014)
Background: Several studies have shown a higher risk of psychological problems in health care workers exposed to serious occupational stressors. Objectives: The aim of the present study was to assess the presence of Post-traumatic Stress Disorder (PTSD) and possible risk factors in a sample of 32 workers who were at the same time rescuers and victims of a fire that broke out in the neonatal intensive care unit of a large paediatric hospital. Methods: Immediately and six months after the event, the subjects underwent a study protocol aimed at the diagnostic assessment of PTSD, investigated via the Clinician-Administered PTSD Scale (CAPS) and the Impact of Event Scale-Revised (IES-R). Results: Out of the 30 subjects examined (two were missing), six showed the diagnostic criteria for a current PTSD. Risk factors for PTSD onset were a prior psychiatric disorder, the level of involvement in the fire disaster and the presence of phobias in the days immediately after the event. Gender and level of education approached statistical significance. Conclusions: The high prevalence of PTSD found in this sample was due to the fact that the risk of death or serious injury involved infants.